Introduction: Towards a global history of paleontology: The paleontological reception of Darwin's thought. (December 2017) - Sepkoski, David; Tamborini, Marco
Highlights: Paleontology had an important role in the reception of Darwinian evolutionary ideas. The reception of Darwin by paleontologists varied significantly by national tradition. This special issue is a first step towards a global history of paleontology.